2018
DOI: 10.3389/fnmol.2018.00455
|View full text |Cite
|
Sign up to set email alerts
|

microRNAs Sculpt Neuronal Communication in a Tight Balance That Is Lost in Neurological Disease

Abstract: Since the discovery of the first microRNA 25 years ago, microRNAs (miRNAs) have emerged as critical regulators of gene expression within the mammalian brain. miRNAs are small non-coding RNAs that direct the RNA induced silencing complex to complementary sites on mRNA targets, leading to translational repression and/or mRNA degradation. Within the brain, intra- and extracellular signaling events tune the levels and activities of miRNAs to suit the needs of individual neurons under changing cellular contexts. Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 296 publications
(348 reference statements)
0
49
0
Order By: Relevance
“…The only predicted activated state was identified in S1.3 (activation z-scores of 2.000; 5.280 and P value of overlap 1.68E-05; 7.28E-05). In our S2.3 findings, miR-137-3p was an upstream regulator of ADRB1, ASPH, CACNB2 [36], CTNA3 [37], GREM1 [38], and ZEB2 (an ELAVL1 [41]. In the schizophrenia upstream regulator comparisons, all miRNAs were activated (S1.3, S3.3), while in S2.3, of 2 miRNAs represented, neither was activated.…”
Section: )mentioning
confidence: 61%
“…The only predicted activated state was identified in S1.3 (activation z-scores of 2.000; 5.280 and P value of overlap 1.68E-05; 7.28E-05). In our S2.3 findings, miR-137-3p was an upstream regulator of ADRB1, ASPH, CACNB2 [36], CTNA3 [37], GREM1 [38], and ZEB2 (an ELAVL1 [41]. In the schizophrenia upstream regulator comparisons, all miRNAs were activated (S1.3, S3.3), while in S2.3, of 2 miRNAs represented, neither was activated.…”
Section: )mentioning
confidence: 61%
“…Intercellular communication of miRNA is essential for normal tissue functioning, and interruptions of this process are shown to induce neuronal deficits [88]. Previous studies have identified the inhibition of glia-neuron directional communication of miR-155 in a culture system to increase neuronal viability [44].…”
Section: Mir-155 Potentially Translocates Between Glia and Neurons Inmentioning
confidence: 99%
“…In neurons, miRNA levels are subject to regulation by external cues. For example, sensory experience, synaptic activity, and glutamatergic signaling have been reported to induce specific miRNAs [4][5][6][7][8][9][10][11][12] which enable structural and functional plasticity by fine tuning the levels of plasticity-related genes [4,[13][14][15]. However, miRNAs are also upregulated under pathological conditions like ischemia, spinal cord injury, neurodegenerative diseases, and neuropsychiatric disorders [16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%